2015
DOI: 10.1089/bfm.2015.0069
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Depressive Symptoms and Breastfeeding: A Prospective Cohort Study

Abstract: Depressive symptoms during pregnancy appeared to be associated with early breastfeeding cessation for mothers residing in Sabah.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
7
3
Order By: Relevance
“…Surprisingly, despite our sample reporting concerning rates of mental disorders, depression and other mental disorders were not significant predictors of negative breastfeeding outcomes as previously reported 4648 . Depression may need further investigation as a predictor for breastfeeding initiation among HIV-infected mothers, as our findings showed a trend towards significance.…”
Section: Discussioncontrasting
confidence: 86%
“…Surprisingly, despite our sample reporting concerning rates of mental disorders, depression and other mental disorders were not significant predictors of negative breastfeeding outcomes as previously reported 4648 . Depression may need further investigation as a predictor for breastfeeding initiation among HIV-infected mothers, as our findings showed a trend towards significance.…”
Section: Discussioncontrasting
confidence: 86%
“…Increased depressive symptoms are also associated with no engagement in favorable health practices during pregnancy [27]. A cohort study in Malaysia revealed that women with antenatal depression were more likely to stop breast feeding before six months than their counterparts [28].…”
Section: Introductionmentioning
confidence: 99%
“…Women who experience elevated depressive symptoms during the perinatal period tend to terminate breast feeding earlier. [30][31][32] Most (9/10) studies included in a recent meta-analysis found that postpartum depressive symptoms occurred prior to early breast-feeding discontinuation. 32 However, negative breast-feeding experiences can also precede onset of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%